The Dominant Factors of High Scabies Incidence In Indralaya Islamic Boarding School Students South Sumatera, Indonesia - Salvari Gusti Ayu Dwi Putri; Ahmad Ghiffari; Chairil Anwar; Rico Januar Sitorus (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Scabies is a skin disease caused by infestation towards Sarcoptes scabiei, the condition locally known as